Quantum size effects on magnetism in Eu2MnHfO6 nanoparticles: Role of surface-to-volume ratio, magnetic blocking, and magnetic phase transitions - Sibusiso Nqayi; Buyisiwe Sondezi (Results in Physics)
In this paper, we investigate the quantum size effects on Eu2MnHfO6 (EMHO) nanoparticles (NPs) synthesized via sol–gel and annealed at 500, 800, and 1000 °C. XRD confirmed a cubic Fd3̅m structure across all samples, with NP sizes increasing from 7.4  nm to 23.8  nm. Smaller NPs displayed features of quantum dots (QD) and weakened Mn/Hf–O–Mn/Hf bonding due to broken surface coordination, as seen in FTIR spectra. Magnetic measurements revealed size-dependent behaviour: smaller NPs exhibited surface-driven phenomena like blocking temperature (TB) and surface spin effects (TSE), while larger NPs (23.8  nm) showed bulk-like super-exchange interactions with distinct Néel (TN) and Curie (TC) temperatures. Local magnetic inhomogeneities indicating a Griffiths phase (GP) were found in the smallest and largest particles, overlapping with TC. These novel results underscore how surface-to-volume ratios influence magnetic transitions, supporting a modified Curie–Weiss law that distinguishes surface and volume effects with coordination variations in MNPs.